LITERASI SEBAGAI KUNCI UNTUK MENGATASI KETIMPANGAN SOSIAL: STUDI KOMPARATIF ANTARWILAYAH DI KOTA TASIKMALAYA - Angelica Kezya Mutiara Sesa Batubara; Wulan Nur Aini; Ichsan Fauzi Rachman (CV. Adiba Aisha Amira, 2024)
This research examines the role of literacy in overcoming social inequality in Tasikmalaya City. Inequalities in access to education, economics and health, as well as low literacy awareness are the main focus. Through comparative studies between regions, this research aims to identify factors that influence literacy and social inequality, as well as develop strategies to increase literacy and reduce social inequality. This research combines quantitative and qualitative approaches to gain a comprehensive understanding. Data was collected through surveys and in-depth interviews in various regions. The research results show that literacy has a positive impact on welfare and reduces social inequality. Areas with high literacy levels have better access to education, employment and public facilities. Literacy plays an important role in improving welfare and reducing social inequality. Efforts to increase literacy in Tasikmalaya must focus on interesting and innovative programs, easy access to books, improving the quality of literacy education in schools, and building public awareness. Digital literacy is also important to open up new opportunities and protect ourselves in the modern era.